The adaptive thermal comfort of individual performance working at home - Ongkowiyono, Jocelyn Octavia; Budianto, Geby Nathasha Tiffany; Armelia, Elizabeth Ferren; Ongkowiyono, Vio Angelina; Mediastika, Christina Eviutami (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Eco-friendly architecture (EFA) is a design approach to produce healthy and comfortable buildings. In the pandemic era and in years to come when working from home is a trend, a healthy and comfortable home is crucial because people spend their time at home. Thermal comfort is considered the most significant comfort factor for building occupants, especially at home. This paper reports a study on the relationship between thermal comfort, individual performance, and productivity while working at home. Data was collected qualitatively through observation, heat transfer calculation, and in-depth interviews. This study concludes that a thermally comfortable house that follows the EFA concept is an aspect that influences performance and productivity. However, thermal comfort is not the only aspect related to comfort. Habits and adaptation of occupants to certain conditions also affect comfort, which leads to good performance and productivity. Occupants feel comfortable doing office and household tasks at home due to their adaptation to the surrounding thermal comfort based on their preferences.